Strategi Komunikasi Verbal dan Nonverbal Guru terhadap Anak Didik Autis di Yayasan Tali Kasih Medan - Panggabean, Trie Tifany Natasha (JURNAL SIMBOLIKA: Research and Learning in Communication Study, 2019)
This paper discusses the teacher's verbal and nonverbal communication strategies towards autistic students at the Tali Kasih Foundation. Autistic children have strange behaviors that don't seem to care about their surroundings and tend to be alone as if they live in a different world. This behavior occurs because of nerve damage in the part of the brain that results in impaired social abilities, unstable emotions and speech disorders. Tali Kasih Foundation is a school that provides therapeutic services for autistic children. The purpose of this study was to describe the teacher's verbal and nonverbal communication strategies towards autistic students at the Tali Kasih Foundation and to describe the scattering in teaching autistic children. This study used a descriptive qualitative research method with an analysis of teacher verbal and nonverbal communication. The method of data collection is obtained by participant observation and interviews. The technique of determining informants purposively, the main informants in this study were teachers who had teaching experience of at least a year at the Tali Kasih Foundation. An important finding that can be seen from this research is that the teacher's verbal and nonverbal communication strategies influence the acceptance of program material messages on autistic children and the way teachers deal with obstacles in teaching autistic children to determine the teaching outcomes that have an impact on their development.